2020
DOI: 10.3390/jcm9072265
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptides, Cognitive Impairment and Dementia: An Intriguing Pathogenic Link with Implications in Hypertension

Abstract: The natriuretic peptides (NPs) belong to a family of cardiac hormones that exert relevant protective functions within the cardiovascular system. An increase of both brain and atrial natriuretic peptide levels, particularly of the amino-terminal peptides (NT-proBNP and NT-proANP), represents a marker of cardiovascular damage. A link between increased NP levels and cognitive decline and dementia has been reported in several human studies performed both in general populations and in cohorts of patients affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Publications in the last few years have also reported a link between BNP levels and the development of dementia. In these observations, BNP appears as a marker of cardiac dysfunction underlying subclinical brain damage and, consequently, dementia [15]. We also observed that patients presenting with peri-infarct CI scored significantly higher on the SYNTAX scale assessing the complexity of atherosclerotic lesions in the coronary arteries.…”
Section: Discussionsupporting
confidence: 63%
“…Publications in the last few years have also reported a link between BNP levels and the development of dementia. In these observations, BNP appears as a marker of cardiac dysfunction underlying subclinical brain damage and, consequently, dementia [15]. We also observed that patients presenting with peri-infarct CI scored significantly higher on the SYNTAX scale assessing the complexity of atherosclerotic lesions in the coronary arteries.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, HRF added predictive value to models that in addition to the variables mentioned above also included serum concentration of NT-proBNP. This analyte has been reported to be associated with incident dementia in MESA (Ostovaneh et al, 2020) and other studies (Nagata et al, 2019), with MRI measures of cognitive function and structure (Zonneveld et al, 2017;Ferguson et al, 2018), as well as, with overall or some domains of cognitive impairment (Kerola et al, 2010;Ferguson et al, 2018;Gallo et al, 2020).…”
Section: Discussionmentioning
confidence: 75%
“…48 Other possible mechanisms linking LAV to cognition include an adaptive response to endothelial dysfunction 47 and increased levels of atrial natriuretic peptide. 49 Our study has some limitations that are worth noting. Echocardiograms were performed 25 years apart using slightly different procedures and equipment, which may affect the comparability of the echocardiographic parameters.…”
Section: Discussionmentioning
confidence: 93%
“…48 Other possible mechanisms linking LAV to cognition include an adaptive response to endothelial dysfunction 47 and increased levels of atrial natriuretic peptide. 49…”
Section: Discussionmentioning
confidence: 99%